An "Exotic" Phenomenon for the "Basc" tradition The incorporation of foot-ball in Basque Cultural Nationalism - Molnar, Peter (Huarte de San Juan. Geografía e Historia, 2013)
The consolidation of modern sport activities in the Basque Country that took place in the first decades of the 20th century necessarily required a change of postures by the political parties facing a new social phenomenon. Even though football was conceived as a sport alien in theory to the cultural traditions defended and promoted by Basque nationalism, it achieved to gather supporters among the adherents of the movement practically from its appearance in the banks of the River Nervión. While the launch of the first Spanish sports newspaper under the political umbrella of the Basque Nationalist Party in 1924 demonstrates the rapprochement of Basque nationalism towards modern sports, the incorporation of football in its cultural framework had supposed a notably long process not without ideological conflicts.
Keywords: Basque Nationalist Party; cultural nationalism; modern sports; football